Strategic Bubble Tourism for Sustainable Destination Governance: Policy Readiness, Carrying Capacity, and Community Participation in Bali - Faizal Madya; Nur Ambia Arma; Yos Sudarso; Anita Marianata; Ni Putu Ari Setiawati; Hana Melita Ekasari; Nazya Priyanka Katryna (FOUNDAE (Foundation of Advanced Education), 2027)
Strategic bubble tourism, environmental carrying capacity, collaborative governance, and adaptive destination management are increasingly relevant to Bali as visitor growth intensifies spatial and ecological pressures. This study assesses whether Bali’s provincial policy architecture is ready to support Strategic Bubble Tourism as a capacity-sensitive governance framework. Using a qualitative evaluative case study, the analysis examines spatial-planning regulations, source-based waste-management policies, foreign-tourist levy regulations, official tourism statistics, and published empirical studies through framework analysis. Findings show strong normative foundations but limited operational coupling across four domains: visitor redistribution, carrying-capacity thresholds, shared community authority, and adaptive monitoring with fiscal accountability. The analyzed corpus does not document transparent cluster-level thresholds or decision rules linking capacity signals to visitor-management actions. Strategic Bubble Tourism is therefore best positioned as a diagnostic governance architecture rather than a validated operational model. Its implementation requires explicit cluster boundaries, multidimensional capacity indicators, co-decision mechanisms, interoperable monitoring, and traceable fiscal accountability.